The Factorial Structure and Psychometric Properties of Bullying Prevalence Questionnaire in Secondary Schools - Afzal Akbari-balootbangan; Siavash Talepasand (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Bullying has been common in schools across the world. Therefore, assessing the psychometric properties of its structures is important. The aim of this study was the assessment of the factorial structure and psychometric properties of bullying prevalence questionnaire. Materials and Methods: The present study was descriptive and psychometric. For this purpose, 400 students (200 boys and 200 girls) were selected by multistage cluster sampling method and answered the bullying prevalence questionnaire and subjective well-being inventory (divergent validity). For data analysis, factor analysis method, Cronbach's alpha coefficient and Pearson's correlation test were used by SPSS software version 22 and AMOS version 21. Results: factor analysis result showed that this questionnaire was saturated with three factors and had good fitness scales. Significant negative relationships of bullying prevalence with subjective well-being (r = -0.10 and P ≤ 0.05) and academic achievement (r = -0.18 and P ≤ 0.01) were obtained. Cronbach's alpha for the total scale was calculated as 0.81, and for each of the subscales it was as follows: bullying: 0.81, victim 0.75, and pro-social 0.70; all the scores were satisfactory. Conclusions: Findings of the research showed that the Persian version of the bullying prevalence questionnaire was acceptable among students concerning psychometric characteristic and it can be used as a valid instrument for psychological studies.